The Correlation of Family Support with Diet Compliance and Fluid Restriction in CHF Patients - Dian Elysa Dwihastia; Ismansyah; Frana Andrianur (Formosa Journal of Science and Technology, 2023)
Congestive Heart Failure (CHF) in Indonesian is called Congestive Heart Failure (CHF) is a complex clinical syndrome resulting from a functional or structural heart disorder that interferes with the ability of the ventricles to fill or eject blood. The risk factors that trigger the high number of CHF patients are an unhealthy diet, lack of activity, smoking, and drinking alcoholic beverages. Family support is very important for CHF patients, apart from helping in terms of self-care and therapy, family support is also very necessary in psychological terms. This study aims to determine the relationship between family support and dietary compliance and fluid restriction in CHF patients. The statistical test value was obtained p-value = 0.001 (p <0.05). It can be concluded that there is a significant relationship between family support and dietary compliance and fluid restriction in CHF patients in dr. Abdul Rivai Berau, East Kalimantan.